Status and ecogeographical conditions of Manihot esculenta Crantz in the Las Montañas Region, Veracruz - Del Rosario-Arellano, José Luis; Serna-Lagunes, Ricardo; Andrés-Meza, Pablo; Leyva-Ovalle, Otto Raúl; Cebada-Merino, Miguel; Ángel Capetillo-Burela, Ángel Capetillo-Burela (Ecosistemas y Recursos Agropecuarios, 2024)
The study of the ecogeographic conditions of species of food interest for humans and for animal feeding, such as cassava, has implications for how the species adapts to various edaphoclimatic conditions and generates knowledge about the current state of crop management in an agroecological region. The objective was to analyze the current state and ecogeographic conditions of cassava in the Las Montañas region, Veracruz, Mexico. In nine municipalities of the Las Montañas region, Veracruz, field trips were carried out to collect 13 accessions of cassava, passport data was recorded, which includes information on the donor producer, locality, municipality, and altitude, the uses and management of cassava. With the georeferences, the description of eight pedological variables and 19 climatic variables was carried out using the ecogeography technique. Cassava was reported in backyard gardens, plots, lemon orchards, coffee plantations, sugarcane fields, and banana plantations, in areas that are classified as areas with agricultural, livestock, and forestry management, dedicated to annual and semi-permanent seasonal agriculture and urban spaces. They were found under different types of soil: humic and orthic acrisol, humic andosol, haplic feozem, and chromic vertisol. This study is a pioneer in the ecogeographic characterization of cassava in Las Montañas, Veracruz, but funding is required to carry out fieldwork to increase collection locations, characterize accessions and implement a genetic diversity conservation program.
Keywords: Manihot esculenta Crantz; germplasm; agroecosystems; edaphoclimatic; conservation